Exploratory analysis of one versus two-day intermittent fasting protocols on the gut microbiome and plasma metabolome in adults with overweight/obesity - Mohr, Alex E.; Jasbi, Paniz; Bowes, Devin A.; Dirks, Blake; Whisner, Corrie M.; Arciero, Karen M.; Poe, Michelle; Gu, Haiwei; Gumpricht, Eric; Sweazea, Karen L.; Arciero, Paul J. (Frontiers in Nutrition, 2022)
Nutritional interventions are a promising therapeutic option for addressing obesity and cardiometabolic dysfunction. One such option, intermittent fasting (IF), has emerged as a viable alternative to daily caloric restriction and may beneficially modulate body weight regulation and alter the gut microbiome (GM) and plasma metabolome. This secondary analysis of a larger, registered trial (ClinicalTrials.gov ID: NCT04327141) examined the effect of a four-week intervention comparing one vs. two-consecutive days of IF in combination with protein pacing (IF-P; 4-5 meals/day, >30% protein/day) on the GM, the plasma metabolome, and associated clinical outcomes in overweight and obese adults. Participants (n=20) were randomly assigned to either a diet consisting of one fasting day (total of 36 hours) and six low-calorie P days per week (IF1-P, n=10) or two fasting days (60 hours total) and five low-calorie P days per week (IF2-P, n=10). The fecal microbiome, clinical outcomes, and plasma metabolome were analyzed at baseline (week 0) and after four weeks. There were no significant time or interaction effects for alpha diversity; however, baseline alpha diversity was negatively correlated with percent body fat change after the four-week intervention (p=0.030). In addition, beta-diversity for both IF groups was altered significantly by time (p=0.001), with no significant differences between groups. The IF1-P group had a significant increase in abundance of Ruminococcaceae Incertae Sedis and Eubacterium fissicatena group (q≤0.007), while the IF2-P group had a significant increase in abundance of Ruminococcaceae Incertae Sedis and a decrease in Eubacterium ventriosum group (q≤0.005). The plasma metabolite profile of IF2-P participants displayed significant increases in serine, trimethylamine oxide (TMAO), levulinic acid, 3-aminobutyric acid, citrate, isocitrate, and glucuronic acid (q≤0.049) compared to IF1-P. Fecal short-chain fatty acid concentrations did not differ significantly by time or between groups (p≥0.126). Interestingly, gastrointestinal symptoms were significantly reduced for the IF2-P group but not for the IF1-P group. Our results demonstrate that short-term IF modestly influenced the GM community structure and the plasma metabolome, suggesting these protocols could be viable for certain nutritional intervention strategies.